2016
DOI: 10.1371/journal.pone.0160021
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A Detection on Antibody- Immobilized on BSA-Functionalized Gold Electrodes

Abstract: Ochratoxin A (OTA)—a toxin produced by Aspergillus carbonarius, Aspergillus ochraceus, and Penicillium verrucosum—is one of the most-abundant food-contaminating mycotoxins. To avoid the risk of OTA consumption for humans and animals, the rapid detection and quantitation of OTA level in different commodities are of great importance. In this work, an impedimetric immunosensor for ochratoxin A (OTA) detection, a common toxic botanical contaminant, was developed via the immobilization of anti-OTA antibody on bovin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The antibody solution (100 ng/mL) was then pipetted over the surface (1 h room temperature, humid atmosphere). For the deactivation of the remaining succinimide groups and in order to block unreacted active sites 1 M ethanolamine–HCl was added for 15 min in the dark [ 30 ]. The modified electrodes were stored dry overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The antibody solution (100 ng/mL) was then pipetted over the surface (1 h room temperature, humid atmosphere). For the deactivation of the remaining succinimide groups and in order to block unreacted active sites 1 M ethanolamine–HCl was added for 15 min in the dark [ 30 ]. The modified electrodes were stored dry overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The analytical performance of the electrochemical aptasensor was compared with published studies on the electrochemical detection of OTA, as shown in Table S4. Significantly, the current approach provides a lower LOD and wider working range compared to other silver metallization assays. The LOD of our system is marginally higher than the platforms presented in refs , ; however, it is important to note that the linear range in the current system is much wider and the method far simpler to implement due to the use of disposable SPGEs.…”
Section: Resultsmentioning
confidence: 84%
“…From the results showed above is deducted that by the two types of electrochemical methods using screenprinted carbon electrodes (DPV and CV) and Jenco microelectrodes (for iodide detection), iodide can be easily determined qualitatively and quantitatively. Both methods are safe and easy to use, and can be thought of as a portable system with a wide range of applicability [34][35][36][37][38][39][40] (screen electrodes are already used to detect toxic and bioactive compounds in the life sciences), alongside other validated methods for the same purpose [41][42][43][44][45][46][47]. Redox microelectrodes correlate in a good manner the redox status of the solution with KI concentration.…”
Section: B2 Redox Microelectrodementioning
confidence: 99%